2022
DOI: 10.1007/jhep08(2022)218
|View full text |Cite
|
Sign up to set email alerts
|

The supersymmetric Neveu-Schwarz branes of non-relativistic string theory

Abstract: We construct the basic Neveu-Schwarz (NS) brane solutions of non-relativistic string theory using longitudinal T-duality as a solution generating technique. Extending the NS background fields to a supergravity multiplet, we verify that all solutions we find are half-supersymmetric. The two perturbative solutions we find both have an interpretation as the background geometry outside a string-like object. Correspondingly, we refer to these non-Lorentzian backgrounds as winding string and unwound string solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Lately, effective field theories that arise from nonrelativistic string theory have been intensively studied, leading to novel nonrelativistic gravity and gauge theories [21][22][23][24][25][26][27][28][29][30][31][32][33] (for further references, see the review [34]). In [16,21], it is shown that the spacetime geometry underlying nonrelativistic closed string theory is non-Riemannian and has a codimensiontwo foliation structure.…”
Section: Jhep10(2022)131mentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, effective field theories that arise from nonrelativistic string theory have been intensively studied, leading to novel nonrelativistic gravity and gauge theories [21][22][23][24][25][26][27][28][29][30][31][32][33] (for further references, see the review [34]). In [16,21], it is shown that the spacetime geometry underlying nonrelativistic closed string theory is non-Riemannian and has a codimensiontwo foliation structure.…”
Section: Jhep10(2022)131mentioning
confidence: 99%
“…it is natural to apply it together with the nonrelativistic T-duality transformations 16] to construct new half-BPS background solutions out of known solutions, such as a nonrelativistic version of the well-known D-brane solutions, along the lines of [33]. We expect that these solutions will provide an important input for a top-down construction of nonrelativistic holography.…”
Section: Jhep10(2022)131mentioning
confidence: 99%
“…This observation does not come as a surprise since we do expect that the longitudinal T-duality relation extends beyond the purely bosonic structure to supergravity. This has been shown in more detail in [112,113]. Similarly, there is a natural relation between the additional fermionic S − /T −gauge symmetries in DSNC − supergravity and the fermionic part of the constraint multiplet.…”
Section: Longitudinal T-dualitymentioning
confidence: 69%
“…The rules for the NSNS sector have previously been derived in [7] by performing a worldsheet duality along the lines of [47,111]. Here, we use the more direct approach of [112] to arrive at the same conclusion. The approach developed there is more in line with [110] and thus easily extendable to the Ramon-Ramond sector as we will show in subsection 5.3.4.…”
Section: Non-lorentzian T-dualitymentioning
confidence: 82%
See 1 more Smart Citation